Espiritualidade e a assistência de enfermagem a pacientes em cuidados paliativos: estudo fundamentado na teoria de Jean Watson - Evangelista, Carla Braz (2020)
The attention paid to the spiritual dimension is a recourse of great relevance to the assistance for patients with life threatening diseases. Within this context, the Theory of Human Caring can be used to support the attention paid to the spiritual dimension of patients under palliative care. The present dissertation consisted of four articles. The first one concerns a research of a reflexive kind. It aimed to analyze Jean Watson’s Theory of Human Caring, according to the description model created by Chinn and Kramer. The second one aimed to adapt the Care Factor Survey tool – Care Provider Version, in its reduced form. The third and fourth articles had the following objectives, respectively: to investigate the perception of patients under palliative care about nursing care with regard to the spiritual dimension, in light of the Theory of Human Caring; to analyze the performance of nurses in assistance of patients under palliative care, stressing the spiritual dimension, in light of the Theory of Human Caring. The second article, which is methodological, involved its translation, back translation, consolidation of the tool’s preliminary version by a committee composed of five members, content validation carried out by five raters by calculating the Content Validity Coefficient and Fleiss’s Kappa. It also involved a pilot test featuring ten nursing professionals of the Caring Factor Survey tool – Care Provider Version, in its reduced form. The third article, which is qualitative, was carried out in a hospital, located in the city of João Pessoa, with nineteen patients under palliative care by means of a semi-structured interview. For data analysis, a content analysis technique was used, with the support of the Iramuteq software. The fourth article, which is also qualitative, was carried out with ten nurses who assisted patients under palliative care, in a hospital located in João Pessoa, by means of a semi-structured interview. The empirical data was analyzed through a thematic content analysis. The research did not start until the ethics committee approval of the Lauro Wanderley University Hospital, under the certificate of presentation for ethical consideration number 99964918.0.0000.5183. The tool presented a satisfactory Total Validity Coefficient and the total Kappa was close to perfect. The research, carried out with patients, showed the elements of Human Caring within the nursing practices, aspects related to the beliefs and religious and spiritual practices; and the relationship between teaching and learning between the nurse and the patient under palliative care. The research, carried out with nursing professionals, showed that the spiritual dimension of caring extends through several religious and spiritual practices. Furthermore, these practices are both respected and encouraged. However, there are many difficulties that get in the way of spiritual caring. It is concluded that the Caring Factor Survey tool – Care Provider Version may be used to analyze the nursing care of patients under palliative care. In addition to this, it was verified that the nurses provide human care making use of many elements of the Caritas Process and use some religious/spiritual practices to do so.